Youth citizens: Reflexions on a citizen youth training policy - Martínez, M. Loreto; Silva , Carmen; Morandé, Margarita; Canales, Lilian (Última Década, 2020)
This article analyzes the results of previous studies on the concepts of citizenship and civic exercise aspirations of young Chileans who have, and how these are being addressed by existing programs in our country. The presentation identifies the challenges for the development of education policy and macro-social context that promotes civic education. An analysis is also more specific aspects of citizenship education that arise in existing programs such as: a) creation of a democratic school culture, b) an assessment of citizenship education and the role of adults; c) line between the program, educational project and institutional environment; d) strengthening of the methodologies and equipment implementing e) problematization of poverty; f) extension of these experiences in real life contexts of young people. We analyze the implications for strengthening the educational work in the school and a youth civic education policy